Students' perspectives on the language question in South African Higher Education: the expression of marginalized linguistic identities on Rhodes University students' Facebook pages - Resha, Babalwa (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2019)
The study analyses students' engagement with the language question in South African Higher Education (HE) and their use of African languages on the institutional Facebook pages, namely UCKAR and RHODES SRC, during the student protests of 2015 to early 2017. Extensive use of social media is a salient feature of the protests as indicated by the hashtag prefixes such as #RhodesMustFall and #FeesMustFall. On these platforms, disgruntled students use their multiple languages to interact, establish a sense of belonging and power to challenge different forms of exclusionary institutional culture, including language policies and practices in HE. The research examines and explores students' perspectives on the language question in Higher Education Institutions (HEIs) on the two institutional Facebook pages, and how mother tongue speakers of indigenous African languages use these languages to express their marginalized linguistic identities in HEIs in South Africa. Theoretically, the study uses the notion of linguistic imperialism to provide a broad context for understanding the language question in South African HE and its significance in transformation. The engagement with the language question on the UCKAR and RHODES SRC Facebook pages is carried out from the lenses of citizen sociolinguistics while the new theory of translanguaging offers the analysis on language usage and alternative ways of addressing linguistic hegemony in educational environments. The translanguaging approach has the capacity to demonstrate multi-layered linguistic practices and reflections on the UCKAR and RHODES pages. It is the interest of the researcher to investigate how students with various linguistic and other backgrounds engage the language question and perform linguistic identities. Language usage on the two Rhodes University institutional Facebook pages and its implications on students' engagement with issues, is used to provide insight towards the implementation of multilingualism in the university. The study is virtual ethnographic in nature. Virtual ethnography is an online research method that employs ethnographic research to study online social interactions. To analyse data, the study used a textual analysis technique as it looks at any analysis of texts broadly. Critical Discourse Analysis approach was used to analyse language debates. Purposive sampling was also used to select Facebook posts and comments on the language question and those written in African languages, and interviews were conducted with key members of Rhodes University, to bring forth their perspectives on the institution's language policy and to figure out what plans are put into place to engage students in debates on the language question because students are important stakeholders of the university, and at the same time some of these students are also speakers of indigenous African languages. In general, the research findings have shown that students as users of languages in HEIs are capable of engendering debates that could be used as solutions to the language question and transformation in the South African HEIs. Thus, this study offers a different approach into engaging with students, their perspective and debates through institutional Facebook pages. In addition, it offers students' perspectives on the curriculum of the university and how the university can go about its transformation. This study provides evidence that the use of indigenous African languages by mother tongue speakers of these languages in institutes of higher learning and their related institutional Facebook pages and social media in general, is an expression of marginalized linguistic identities of these language speakers. Sometimes these identities are multiple, and students use different modalities to express them, hence the notion of translanguaging.
Keywords: Language policy -- South Africa -- Makhanda; Language and education -- South Africa -- Makhanda; Sociolinguistics -- South Africa -- Makhanda; Language and languages -- Study and teaching -- Social aspects -- South Africa -- Makhanda; Linguistic rights -- South Africa; Translanguaging (Linguistics); Multilingual education -- South Africa -- Makhanda; Educational change -- South Africa -- Makhanda; South Africa - Makhanda -- Language and languages -- Political aspects; Student movements -- South Africa -- Makhanda; Online social networks -- South Africa -- Makhanda; Rhodes University -- Sociological aspects; Facebook (Firm); UCKAR